Effect of Bokashi Fertilizer and Green Tonik Liquid Fertilizer on the Growth and Yield of Long Bean (Vigna sinensisL.)Parade Tavi Variety - Elisabeth Elisabeth; Puji Astuti (Universitas 17 Agustus 1945 Samarinda, 2018)
The purpose of the research is to study the effect of bokashi fertilizer and Green Tonik liquid fertilizer and its interaction on the growth and yield of long bean plant, as well as to find the proper dosage of bokashi fertilizer and Green Tonik liquid fertilizer concentration for obtaining the best yield of long bean.The research was conducted using Completely Randomized Design (CRD) in 4 x 4 Factorial Experiment and four replications. The factor was the dosage of bokashi fertilizer (B) consisting of 4 levels : no bokashi fertilizer application (b0), 100 g/polybag(b1), 200 g/polybag (b2), and 300 g/polybag(b3). The second factor was the concentration of Green Tonik liquid fertilizer (N) consisting 4 levels : no Green Tonikfertilizer application (n0), 2 ml/ l water (n1), 4 ml/l water (n2), and 6 ml/lwater (n3).The results showed that: (1) the bokashi fertilizer treatment affected significantly on the plant lenght at age 15 days after planting, number of pods and weight of pods per plant, but it did not affect significantly on the plant lenght at age 22, 29 and 36 days after planting, age of plants flowered, and pods lenght; (2)the Green Tonik liquid treatment affected significantly on the plant lenght at age 22, 29, and 60 days after plantingand weight of pods per plant, but it did not affect significantly on the plant lenght at age 15 days after planting, age of plant flowered, and pods lenght; (3) the interaction treatment between bokashi fertilizer and Green Tonik liquid fertilizer affected significantly on the plant lenght at age 15 days after planting, pods lenght, and weight of pods per plant, but did not affect significantly on the plant lenght at age 22, 29, and 36 after planting, age of plant flowered, and number of pods; and (4) the weighest weight of pods per plant was produced in b2n3 treatment of 401,75 g/plant, while the lighest one was produced in b0n0 treatment of 145,75 g/plant.